EFFECT OF IMPLANTING ZERANOL ON GROWTH AND CARCASS CHARACTERISTICS OF AWASSI LAMBS AND GOAT KIDS RAISED UNDER COMMERCIAL CONDITION - & et al, KAK (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The current experiment was designed to investigate the effect of zeranol implantation on lambs and goats’ kids raised under commercial conditions. Ten male Awassi lambs (AL) (4-5 months old) with an average body weight of 33.7 ± 0.5 kg and 10 male black goat kids (GK) (3-4 months old) with an average body weight of 18.8 ± 0.7 kg were used in the experiment. The experiment was conducted in Berebuhar village close to Duhok city in May the 15th, 2019The animals from each group were randomly divided into two subgroups, the first group was the control group and the other group was implanted with 24 mg zeranol. The animals were grown for 43 days and then slaughtered. Growth rate, average daily gain and carcass characteristics were measured. Data were analysed as factorial 2 × 2.  The results showed that implantation both animal groups with zeranol significantly reduced testicular weight by approximately 55 % and 71 % for goat kids and Awassi lambs respectively. Moreover, the results showed that zeranol implantation found to reduce total body fat from 892 to 816g in goat kids and from 3395 to 2856 g in Awassi lambs. It can be concluded that zeranol implantation has an effect on total body fat and fat tissue distribution.